2005
DOI: 10.1097/01.mnm.0000184941.06123.b9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of low activity meta-[131I]iodobenzylguanidine therapy in patients with disseminated neuroendocrine tumours depends on initial response

Abstract: Of the patients treated with low-activity 131I-MIBG 68% had significant benefit for at least 6 months post-treatment. In these patients with progressive and extensive disease this technique provided prolonged progression-free and overall survival with minimal side effects especially if an initial response to treatment was seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 20 publications
6
36
0
1
Order By: Relevance
“…The observed survival of the carcinoid tumor patients in the present study, with a median overall survival of 47 mo, compared favorably with most reported outcomes for similar patient cohorts and with various protocols (23,25,27,32). There are also few other reports of considerably longer survival of patients with carcinoid tumors after 131 I-MIBG treatment (10,11,24), with some evidence suggesting a survival benefit after the administration of higher 131 I-MIBG activities (11,12).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The observed survival of the carcinoid tumor patients in the present study, with a median overall survival of 47 mo, compared favorably with most reported outcomes for similar patient cohorts and with various protocols (23,25,27,32). There are also few other reports of considerably longer survival of patients with carcinoid tumors after 131 I-MIBG treatment (10,11,24), with some evidence suggesting a survival benefit after the administration of higher 131 I-MIBG activities (11,12).…”
Section: Discussionsupporting
confidence: 70%
“…This finding was particularly encouraging considering the difficulty in controlling carcinoid symptoms, which frequently determine patients' quality of life and increase morbidity rates (22). A morphologic tumor response after 131 I-MIBG therapy, on the other hand, was less frequently observed for carcinoid tumors, with reported response rates of 0%-35% (10,11,(23)(24)(25)(26)(27). The main observed outcome in the present study was disease stabilization (with or without minor remission) in 80%-90% of patients.…”
Section: Discussionmentioning
confidence: 53%
“…It is thought that emission of ionising radiation at this site results in tumour decay (Mukherjee et al, 2001;Rose et al, 2003;Pasieka et al, 2004). This therapy has been used to treat NETs of various types, including gastroenteropancreatic NETs (Pathirana et al, 2001;Pasieka et al, 2004;Safford et al, 2004;Sywak et al, 2004;Buscombe et al, 2005), paraglangliomas (Mukherjee et al, 2001;Safford et al, 2003;Fitzgerald et al, 2006), phaeochromocytomas (Castellani et al, 2000;Rose et al, 2003;Safford et al, 2004;Fitzgerald et al, 2006), medullary carcinoma of the thyroid (Castellani et al, 2000(Castellani et al, , 2003Mukherjee et al, 2001) and neuroblastomas (Howard et al, 2005;Matthay et al, 2007). A number of previous studies had demonstrated significant symptomatic benefit in 40 -60% of patients with metastatic NETs following 131 I-MIBG therapy (Safford et al, 2004;Sywak et al, 2004), in a safe and cost-effective manner (Pathirana et al, 2001).…”
mentioning
confidence: 99%
“…In tumours trapping metaiodobenzylguanidine-131 I, the probability of response would be high after administration of therapeutic doses. In a study that included 25 patients 11 , disease stabilization was achieved in 72% of patients after 6 months, with median survival duration being 18 months. In the patients who died, the mean interval between disease progression and death was 4.6 months (range: 0-12 months).…”
Section: Discussionmentioning
confidence: 99%